CAPABILITY OF INDONESIA’S CREATIVE INDUSTRY IN THE ERA OF ASEAN ECONOMIC COMMUNITY (AEC) - Afida Kurnia Yogasari (FISIP UMY, 2016)
This paper is a research about Indonesia’s government towards the creative industry in the era of ASEAN Economic Community (AEC). Officially established since 2005, Indonesia should have proper preparation towards the creative industry, especially while facing the regional economic cooperation such as AEC. Even though Indonesia still has many obstacles in several sectors such as culinary, fashion, craft and publishing, but there is still opportunity for Indonesia compete with other ASEAN Member countries such as Singapore, Malaysia and Thailand.